Ascending speed and nocturnal activity of adult masu salmon (Oncorhynchus masou Brevoort) during upstream migration. Issue 5 (16th September 2020) - Ohkuma, Kazumasa; Abe, Kunio; Kagaya, Manabu; Yamaya, Kazuyuki; Okukawa, Motokazu; Watanabe, Masa‐aki; Yamamoto, Takeo
Abstract: We released five adult masu salmon ( Oncorhynchus masou ) tagged with external transmitters to track their ascending behaviour. The signals of all specimens were recorded in the upper area of the river system. Two patterns of ascending behaviour were recognized: ascending upward immediately after release and ascending during increased river discharge. The fastest ascending speed was about 1000 m h –1 . Active movements were detected at night. The signal recording duration at each receiver for each fish was generally brief. Most fish did not stay at the pools where the receivers were installed.